2018
DOI: 10.1111/apt.14645
|View full text |Cite
|
Sign up to set email alerts
|

Letter: new thresholds need to be defined when using point of care assays to monitor infliximab trough levels in IBD patients

Abstract: Linked Content This article is linked to Papamichael et al paper. To view this article visit https://doi.org/10.1111/apt.14458.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
8
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 5 publications
4
8
1
Order By: Relevance
“…We also found that infliximab and adalimumab concentrations before and after the correction of the HMSA were significantly different, both quantitatively and qualitatively. This is in line with previous studies showing discrepancies among assays used for evaluating biologic drug concentrations [8,9,14,15]. Moreover, we identified adalimumab concentration thresholds of 22.4 µg/mL before the corrected measures and 14.4 µg/mL after the corrected measures discriminated patients with or without treatment failure.…”
Section: Discussionsupporting
confidence: 91%
“…We also found that infliximab and adalimumab concentrations before and after the correction of the HMSA were significantly different, both quantitatively and qualitatively. This is in line with previous studies showing discrepancies among assays used for evaluating biologic drug concentrations [8,9,14,15]. Moreover, we identified adalimumab concentration thresholds of 22.4 µg/mL before the corrected measures and 14.4 µg/mL after the corrected measures discriminated patients with or without treatment failure.…”
Section: Discussionsupporting
confidence: 91%
“…32,145 However, as the number of such tests increases, their quality needs to be assessed and their accuracy compared with the commonly used laboratory measurements of drug concentrations and ADA to check for potential discrepancies. [146][147][148]…”
Section: Point-of-care Assaysmentioning
confidence: 99%
“…In this way, the point of care (POC) for TDM testing could play a key role in a proactive strategy. In addition, the best threshold values are not yet defined and may differ between POC and ELISA assays 4 . Second, we need skill upgrades for gastroenterologists taking care of IBD patients to better interpret the results of TDM in their daily practice.…”
mentioning
confidence: 99%